2022
DOI: 10.1186/s12889-022-14164-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ambient air pollution, obesity, and serum vitamin D status in the general population of Korean adults

Abstract: Background Although a growing body of evidence suggests air pollution is associated with low serum vitamin D status, few studies have reported whether obesity status affects this relationship. The aim of this study was to identify associations between ambient air pollution exposure, obesity, and serum vitamin D status in the general population of South Korea. Methods This study was conducted in a cross-sectional design. A total of 30,242 Korean adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Notably, we discovered that the link between obesity and 25OHD varied across men and women after controlling for confounders, which leads us to believe that sex hormones may have played a role. In studies in Korea and Serbia, obese women were found to be more likely to suffer from vitamin D deficiency [ 29 , 30 ]. However, two studies from India and Norway showed that obese men had a considerably higher frequency of vitamin D deficiency than thin men [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we discovered that the link between obesity and 25OHD varied across men and women after controlling for confounders, which leads us to believe that sex hormones may have played a role. In studies in Korea and Serbia, obese women were found to be more likely to suffer from vitamin D deficiency [ 29 , 30 ]. However, two studies from India and Norway showed that obese men had a considerably higher frequency of vitamin D deficiency than thin men [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we discovered that the link between obesity and 25OHD varied across men and women after controlling for confounders, which leads us to believe that sex hormones may have played a role. In studies in Korea and Serbia, obese women were found to be more likely to suffer from vitamin D de ciency [23,24]. However, two studies from India and Norway showed that obese men had a considerably higher frequency of vitamin D de ciency than thin men [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…78 Obesity is at risk of VDD because of higher body mass index and vitamin D is a fat-soluble vitamin leading to the dilution and causing low plasma levels of 25(OH)D. 66,78 Recent studies had shown that long term exposure to ambient PM, NO 2 , and CO was associated with decreased 25(OH)D. [80][81][82] According to recent evidence, females had a higher chance to develop VDD more than males. 80,[82][83][84][85] Then living in an area of high air pollution results in a decrease in the skin's ability to produce vitamin D leading to VDD. 74,78 Active form of vitamin D has abilities to inhibit cellular proliferation, induce terminal differentiation, inhibit angiogenesis, stimulate insulin production, inhibit renin production, and apoptosis.…”
Section: Vitamin D Air Pollution and Effects On Organ Transplantationmentioning
confidence: 99%
“…Recent studies had shown that long term exposure to ambient PM, NO 2 , and CO was associated with decreased 25(OH)D 80–82 . According to recent evidence, females had a higher chance to develop VDD more than males 80,82–85 . Then living in an area of high air pollution results in a decrease in the skin's ability to produce vitamin D leading to VDD 74,78 …”
Section: Introductionmentioning
confidence: 99%